A novel procedure to investigate social anxiety using videoconferencing software: A proof-of-concept study. (October 2022) - Huneke, Nathan T.M.; Rowlatt, Hannah; Hyde, Joshua; McEwan, Alexander; Maryan, Louise; Baldwin, David S.; Garner, Matthew
Highlights: We developed a novel experimental paradigm to investigate Social Anxiety Disorder that can be carried out entirely online (the InterneT-based Stress test for Social Anxiety Disorder; ITSSAD). The entire protocol can be carried out by a single investigator, reducing costs and ensuring internal reliability. In a non-treatment-seeking sample of volunteers with social anxiety symptoms, the ITSSAD induced significant subjective anxiety and reduced positive affect. Increased trait social anxiety symptoms predicted increased anxiety following the ITSSAD, while trait generalized anxiety did not. The ITSSAD is a new tool for researchers to investigate mechanisms underlying social anxiety disorder. Abstract: Social anxiety disorder (SAD) is very common and can be significantly disabling. New treatments are needed as the remission rate for SAD is the lowest of all the anxiety disorders. Experimental medicine models, in which features resembling a clinical disorder are experimentally induced, are a cost-effective and timely approach to explore potential novel treatments for psychiatric disorders. Following the emergence of SARS-CoV-2, there is a need to develop experimental medicine models that can be carried out remotely. We developed a novel procedure to investigate SAD (the InterneT-based Stress test for Social Anxiety Disorder; ITSSAD) that can be carried out entirely online by a single investigator, potentially reducing costs and maximising internal reliability. The procedure involves an anticipatory period followed by a naturalistic social interaction task. In a sample of 20 non-treatment-seeking volunteers with symptoms of SAD, the ITSSAD induced significant subjective anxiety and reduced positive affect. Further, increased social anxiety symptoms at baseline predicted increased anxiety during the social interaction task. This protocol needs further validation with physiological measures. The ITSSAD is a new tool for researchers to investigate mechanisms underlying social anxiety disorder.